Evaluation of post-operative complications associated with tobacco use in thoracic surgery patients - Degirmenci, Mehmet; Kus, Celal (International Surgery Journal, 2021)
Background: Tobacco can make thoracic diseases more complicated by affecting their respiratory functions. Smoking causes many diseases that require surgical treatment and affects surgical results. The aim of the study was to determine the relationship between tobacco use and post-operative complications in thoracic surgery patients and contribute to public health. Methods: In this study, 754 patients were evaluated retrospectively. Patient characteristics and tobacco use habits of the patients were determined. Postoperative complications, admission to the intensive therapy unit, intubation, death, and length of stay in hospital were defined as surgical outcomes. These results were compared and analyzed with tobacco use. Results: The patients consisted of 536 (71.1%) men and 218 (28.9%) women. Tobacco use was more common in men (X2=223.216, p<0.001) and younger ages (X2=45.342, p<0.001). Complications occurred in 96 patients, 76 (79.2%) of whom used tobacco. Tobacco use (p<0.001, OR=3.547), ASA score (p=0.029, OR=2.004), major surgeries (p<0.001, OR=4.458), and minimally invasive surgeries (p=0.027, OR=2.323) are associated with complications. Length of hospital stay is related to the amount of tobacco (p<0.001, OR=3.706), size of surgery (p<0.001, OR=14.797), over 65 years (p<0.001, OR=2.635), and infectious diseases (p=0.039, OR=1.939). Conclusions: Tobacco use is related to poor outcomes in thoracic surgery patients, and it is a severe health problem, especially at young ages. Tobacco control programs should be supported to prevent the effects of tobacco use on thoracic diseases and postoperative complications.